Monopoli Sumber Daya Alam dan Tergerusnya Livelihood Masyarakat di Desa Sebamban Baru Kabupaten Tanah Bumbu - Dwi Mariatul Syadiah; Ismar Hamid (Prodi Sosiologi FISIP ULM, 2023)
Natural resource monopoly packaged in the form of delegation of management rights from the state to companies has resulted in complex problems, which have led to the erosion of people's livelihoods. This study aims to determine the form of monopoly on natural resources carried out by companies in the perspective of the greedy theory and how it impacts the people's livelihood from the perspective of ecological transformation. This study uses qualitative research with a case study research type. Data collection techniques using observation, interviews and documentation. The results of the study show that the form of natural resource monopoly in Sebamban Baru Village started with the granting of forest management rights to PT. Kirana Equator. Furthermore PT. Kirana Khatulistiwa transferred management rights to PT. HRB and PT. BIB. Then PT. HRB planted acacia, while PT. BIB uses it for mining activities. In this case, the community has no power in determining the direction of natural resource management in Sebamban Baru Village. Management of natural resources carried out by PT. BIB has led to the erosion of community livelihood sustainability, one of which is due to river pollution from insufficient company waste storage so that it spills into the river. This condition led to the difficulty of clean water being faced by the community and the loss of the community's economic resources from the river. Meanwhile, natural resources management carried out by PT. HRB resulted in the loss of the community's source of life from the land claimed by PT. HRB. Where land managed by the community is declared included in the HTI concession. As a result, people have lost access to land for farming and other economic resources. The monopoly on natural resources leaves an impact on the declining level of the people's economy due to the loss of economic resources that play an important role.